SPATIOTEMPORAL VARIATIONS OF THE S-WAVE ATTENUATION FIELD IN SOURCE ZONES OF STRONG EARTHQUAKES IN THE TIEN SHAN REGION: EVIDENCE FROM THE RECORDS OF UNDERGROUND NUCLEAR EXPLOSIONS - Kopnichev Yu.F.; Sokolova I.N. (My University, 2004)
Spatiotemporal variations of the S-wave attenuation field in the Earth's crust of the Tien Shan region were studied from the records of underground nuclear explosions at the Semipalatinsk nuclear test site. It is shown that anomalously strong changes in the attenuation field structure are observed for the paths that cross or pass near the source zones of strong earthquakes (M ≥ 6.8). We suggest that this phenomenon is related to the ascent of mantle-derived fluids (first of all, water) into the Earth's crust before strong earthquakes and their subsequent lateral migration from the source zones.